Persepsi Guru Geografi Terhadap Kurikulum Merdeka di Sekolah Menegah Atas (SMA) Kabupaten Solok Selatan - Romi Hardianto; Ade Irma Suryani; Momon Dt Tanamir (STKIP PGRI Sumatera Barat, 2023)
The background of this research is the geography teacher's perception of the Merdeka curriculum, which has not been implemented evenly in all SMA schools in Solok Selatan district. The purpose of this research is to find out the perceptions of teachers seen from their absorption, understanding and evaluation of the independent curriculum at SMA Solok SelatanThe type of research used in this research is descriptive. The population in this study were all geography teachers at SMA Solok Selatan, totaling 17 geography teachers. In this study using total sampling. The sample in this study were all geography teachers in Solok Selatan district. data analysis techniques in this study using descriptive analysis techniquesBased on the results of this study, it can be concluded that 1). Teacher perceptions seen from the absorption of the independent curriculum at Solok Selatan High School have a percentage of 87% with good qualifications. 2). The teacher's perception seen from the understanding of the independent curriculum at Solok Selatan High School has a percentage of 85% with a Good qualification. 3). Teacher perceptions seen from the assessment or evaluation of the independent curriculum at Solok Selatan High School have a percentage of 83% with good qualifications.